Illicit Drug Use and Problem Gambling. (25th August 2013) - Ferentzy, Peter; Wayne Skinner, W. J.; Matheson, Flora I.
Abstract : Problem gambling, substance use disorders, and their cooccurrence are serious public health concerns. We conducted a comprehensive review of the literature to understand the present state of the evidence on these coaddictions. Our main focus was illicit drug use rather than misuse of legal substances. The review covers issues related to gambling as a hidden problem in the illicit drug use community; prevalence, problem gambling, and substance use disorders as kindred afflictions; problem gambling as an addiction similar to illicit drug use; risk factors and problems associated with comorbidity, and gender issues. We end with some suggestions for future research.